2008
DOI: 10.1186/1475-2891-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid status and behavioural symptoms of Attention Deficit Hyperactivity Disorder in adolescents: A case-control study

Abstract: Background: Most studies of Attention-deficit hyperactivity disorder (ADHD) have focused on either young children or older adults. The current study compared 11 ADHD adolescents with 12 age-matched controls. The purpose was to examine differences in dietary intake, particularly of essential fatty acids, and determine whether this could explain the typical abnormalities in red blood cell fatty acids observed in previous studies of young children. A secondary purpose was to determine if there were relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 34 publications
5
101
2
1
Order By: Relevance
“…It is known from observational studies that the levels of ω-3 fatty acids such as ALA and DHA, but also of ω-6 fatty acids such as AA, are lower in the erythrocytic membrane phospholipids and plasma of children and adults with ADHD symptoms as opposed to healthy individuals [5,32,34,83,84,121,123,141]. The PUFA levels in the phospholipids of the erythrocytic membranes are most suitable for assessing the PUFA status within the organism.…”
Section: Results From Observational Studiesmentioning
confidence: 99%
“…It is known from observational studies that the levels of ω-3 fatty acids such as ALA and DHA, but also of ω-6 fatty acids such as AA, are lower in the erythrocytic membrane phospholipids and plasma of children and adults with ADHD symptoms as opposed to healthy individuals [5,32,34,83,84,121,123,141]. The PUFA levels in the phospholipids of the erythrocytic membranes are most suitable for assessing the PUFA status within the organism.…”
Section: Results From Observational Studiesmentioning
confidence: 99%
“…Bununla birlikte, YA dağılımı, n-3 YA eksikliğini yansıt-mamaktadır. Adölesan DEHB hastalarının aynı yaştaki kontrol grubu ile diyet alımı farklılıklarının karşılaştırıldığı bir çalışmada (40), DEHB grubunun daha fazla enerji ve yağ tükettiği ancak antropometrik öl-çümlerinin benzer olduğu görülmüştür. DEHB'li çocuklar, kontrollerle eşdeğer miktarlarda omega-3 ve omega-6 yağ asitleri tüketirken, vü-cutta DHA (22: 6n-3) ve toplam omega-3 yağ asitleri düzeyi düşük, omega-6 yağ asitleri yüksek ve n-3:n-6 oranı kontrollerden daha dü-şük bulunmuştur.…”
Section: Dehb'de Yağ Asitleriunclassified
“…Numerous reports of adverse reactions to stimulants in medicated and nonmedicated children (Sonuga-Barke et al 2009), growth and development changes in nonmedicated children (Ptacek et al 2009), and severe side effects in different variants of ADHD (Gruber et al 2009) provide enough rationale to invest in alternative therapies. For example, results of different studies suggest that zinc (Arnold et al 2000(Arnold et al , 2005, omega-3 fatty acids (Colter et al 2008;Johnson et al 2009b;Vaisman et al 2008), L-carnitine (Torrioli et al 2008), iron (Konofal et al 2008, flax oil, and vitamin C (Joshi et al 2006) supplements may be important for treatment of ADHD. A randomized controlled trial that assessed the efficacy of a restricted elimination diet in reducing symptoms in an unselected group of children with ADHD concluded that a strictly supervised elimination diet may be a valuable instrument in testing young children with ADHD on whether dietary factors may contribute to the manifestation of the disorder and may have a beneficial effect on the children's behavior (Pelsser et al 2009b).…”
Section: Future Directions Of Adhd Theorymentioning
confidence: 99%